EVALUASI PERDA NOMOR 3 TAHUN 2009 TENTANG RETRIBUSI PELAYANAN DI BIDANG PERHUBUNGAN DARAT (STUDI KASUS:TARIF PARKIR DI TEPI JALAN UMUM KOTA PEKANBARU) - Meillsy Mitra Pratiwi; Zaili Rusli. SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Acceptance levy Park in the city of Pekanbaru fluctuating expanded in the last 5 years has increased and decreased and did not reach the target due to the large number of interpreter Still doing parking irregularities and act wild parking by the existence of Perda Pekanbaru number 3 in 2009 About Levy's service in the field of Land Transport with the goal of Retribution that Levy and service charge is the original source of income an important Area. The purpose of this research was to evaluate the Perda No. 3 in 2009 About Levy's service in the field of Land Transport Levy specifically about the Organization of parking at the curb and to know the common factors that affect the evaluation of Perda No. 3 in 2009 About Levy's service in the field of Land Transport in particular in Retribution the inaugural at the edge of the road.The concept of the theory is a theory that the author use Dunn, there are 6 (six) evaluation indicators, namely: effectiveness, efficiency, sufficiency, equity, responsiveness, and accuracy policies. This research uses qualitative research methods with the study of descriptive data. In data collection, the author uses interview techniques, observation and documentation. With the use of key informants as a source of information and technique of triangulation as a source in the validity of the data.From the results of the qualitative analysis of descriptive data from the evaluation, rule number 3 2009 Areas of Levy of service in the field of Land Transport (case study on the curb parking rates in General) are categorized yet feels maximum, evidenced from the still high number of violations and irregularities committed by the interpreter with the parking levy rates in excess of parking Ordinance that is in the local regulations for personal gain. Factors that hinder this perda evaluation is still lack of supervisory officers, the lack of availability of land, the lack of participation of the people and the Act of thuggery.Keywords: evaluation, Parking, parking Rates at the edge of public roads